Penerapan Strategi Pembelajaran Berbasis Genius Learning dalam Meningkatkan Aktivitas Hasil Belajar Siswa pada Pembelajaran PKn - Samawati, Samawati (Universitas Negeri Medan, 2014)
This research aims to examines whether using genious-based learning strategy could increase learning activity in the subject of civic education for students in the eleventh grade department of electro in SMK 1 of Lhoknga in 2013/2014 school year. The action research has two cycles in which each cycle consists of four stages such as planning, implementing and observation, reflecting and revising. The subject of the research is 17 studentsÂ in the eleventh grade department of electro in SMK 1 of Lhoknga, Aceh Besar Regency, Province of Aceh. The data have been collected are test result and observation sheet of learning activity. Based on the result could be concluded that genious-based learning strategy can be used as s strategy to increase studentâs learning activity, learning outcomes, and increase the quality of learning processes held by teacher in which learning activity, learning outcome, and teacherâs ability, might be elvate in every cycle. The learning activity increased from 64.71 percent at the first cycle (category sufficient) became 72.9 percent with good category at the second cycle. While the teacherâs ability in the teaching-learning processes increased from 62.5 percent with sufficient category at te first cycle to 72.9 percent with good category at the second cycle. As the learning oucome increased from 64.71 pecent with category passed at the first cycle to 82.35 percent with category passed at the second cycle.